Modular word games for enriching the vocabulary of grade six fast learners - Tangonan, Priscila G. 1946-; Baldo, Trinidad C. (Quezon City College of Education, University of the Philippines Diliman, 1976)
The purpose of the study is to present modular word games that can be used for enriching the vocabulary of Grade Six fast learners. The fifteen modules were organized and prepared to provide a wide range of experiences which would stimulate the fast learners' verbal abilities. Additional enrichment activities, both horizontal and supplementary, were also provided for them to optimally profit from the modules.
Vita.
Thesis (Master of Arts in Teaching - Special Education : Giftedness)--University of the Philippines, Diliman
Keywords: Gifted children -- Education (Elementary) -- Philippines; Word games -- Philippines; Vocabulary